Seasonal and spatial overlap in activity between domestic dogs and dingoes in remote Indigenous communities of northern Australia. Issue 4 (4th January 2021) - Gabriele‐Rivet, V; Brookes, VJ; Arsenault, J; Ward, MP
Abstract : Free‐roaming domestic dogs in Indigenous communities of northern Australia have the potential to spread diseases at the wild–domestic dog interface. Hunting activities with domestic dogs, commonly practiced in Indigenous communities, also create opportunities for wild–domestic dog interactions in the bush, providing pathways for potential disease spread. Data from a camera‐trap study conducted in remote Indigenous communities of northern Australia were used to explore spatial and seasonal opportunities for interactions between dingoes and unsupervised domestic dogs. For each type of dog, activity indices, based on detection events per camera station with an adjustment for sampling effort, were mapped across the study area and plotted against distance to communities. Unsupervised domestic dogs were mostly active in proximity (<1 km) to the communities. However, there was a noticeable peak of activity further in the bush away from the communities, especially in the wet season, coinciding with areas commonly used for hunting activities. In contrast, the activity of dingoes was more homogeneous within the study area, with a higher peak of activity around the communities during the dry season, and in bush areas distant (>10 km) to communities during the wet season. Overall, our findings suggest that interactions between dingoes and unsupervised community dogs are more likely to occur around the communities, particularly during the dry season, whereas in the wet season, there is increased opportunity for interactions in distant areas in the bush between dingoes and, presumably, hunting dogs.